Aadhar Card Based Double Identity Verification System for Railway - Gupta, Saumya; Singh Sandhu, Jaspreet; Deep, Vikas; Sharma, Purushottam (International Journal of Engineering and Technology, 2018)
â€œThe reservation system of the Indian Railways is an enormous database system dealing with about millions of passengers everyday. Many of these passengers travel with a reservation however a lot more travel with unreserved tickets. InÂ this measureless system, it is an extraordinary task to competently handle this data, which is the basic demand of theÂ management. The problems with the existing scenario are Corruption, User Authentication Security Issues, Over population, Inefficient Railway Management. This paper presents an approach to tackle these problems in a much efficient manner. In caseÂ of Indian Railways, detailed passenger data is handled for reservations and in order to provide fast and efficient services, the data has to be processed and verified at a fast pace. For the Indian railways, enhancing the existent system with ADHAAR Card Identification will reduce manual intervention to a great extent. Also the verification of the passengers would be comprehensive and safe. The ADHAAR Card Based railway System will handle the passenger data more effectively and easilyâ€.Â Â